Placebos in the era of open‐label trials: An update for clinicians. (1st November 2018) - Sagy, Iftach; Abres, Jonathan; Winnick, Ariel; Jotkowitz, Alan
Abstract: Placebos have been used extensively by vast numbers of physicians, in a majority of clinical trials. Placebo effects involve behavioural, psychological and genetic factors and have been subject to ethical controversies stemming from the use of deception in treating patients. The patient‐physician encounter, endogenous pharmacological pathways, personality traits and genetic diversity have all been reported to be key players in placebo responses. In the last decade, a new methodological paradigm of placebo research has emerged, using open‐label placebos to investigate their effects which showed promising results for various common medical conditions. In this review, we will summarize the current body of evidence on placebos in clinical practice, with a view to open‐label placebo trials in particular. It is our view that future larger‐scale randomized blinded open placebo trials will benefit physicians and improve patient outcomes.